Extraction, Isolation, Characterisation and Antioxidant Activity Assay of Catechin Gambir (Uncaria gambir (Hunter). Roxb - Ningsih, Edin; Rahayuningsih, Sri (Al-Kimia, 2019)
Catechins are one of polyphenol compounds which reported have antioxidant properties. This study aims to extraction, isolation, characterization, and determine the antioxidant activity of catechin compounds from gambier powder(Uncaria gambir (Hunter). The extraction method used was maceration extraction with three types of solvents (70% ethanol, 70% methanol, and ethyl acetate). The process of purifying catechins is carried out with water, ethyl acetat, and n-hexane. Catechins were characterized by FTIR (Fourier Transform Infra Red) and UV-Vis spectrophotometer and tested for antioxidant activity using the DPPH (2.2 Difenyl -1-Pikrilhidrazil) method. The results showed that the extracted gambier using 70% ethanol solvent resulted in more catechins (51.20 g) than the 70% methanol solvent (40.35 g) and ethyl acetate (16.40 g). Characterization of catechin using UV-Vis spectrophotometer showed that purity content of catechins obtained from the extract ethanol 70% had purity 70.76%, methanol 70% 70.86%, and ethyl acetate 70.35%. Analysis using FTIR showed catechin has functional groups such as hydroxy (-OH), vibration C = C alkene, C-H, CH2 and C-O, so that the compound isolated has the basic structure of the catechin. The result of antioxidant activity from showed IC50 value are 2.72 ppm; 3.04 ppm and 3.06 ppm for extract catechin of etanol 70%, methanol 70% and ethyl acetate, so that can be said that catechins have antioxidant activity levels in a very strong category.